Ode in Onia: Reading the Use of Myth and Twinhood in Diana Evans’ 26a - Kaze, Douglas E. (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
Postcolonial writers have over time engaged in the use of folklore preserved from their precolonial heritage in their works that try to understand the complexities of their postcolonial existence. Such writers have used ancient stories, songs, proverbs and other ideas from their vernacular cosmologies in intertextual conversation with their fiction. In this article, I discuss this kind of practice in the novel 26a by Nigerian-British novelist, Diana Evans. The novel explores personal experiences of twinhood which also raises questions about identity, transnationalism and migration. This paper’s focus is on the ways in which Evans fetches material from her Nigerian background – the myth about twinhood – and merges it with her fiction, allowing both to engage and transform each other. Through this she has not only created a work of magical realism, but finds an effective means to represent trauma, psychic and existential struggles along with what it means to exist between categories.